Perancangan Iklan Kampanye Service City Dengan Menggunakan Teknik Animation Explainer Guna Mengenalkan Pelayanan Publik - Saderi, Eko Cahyono; Bahruddin, Muhammad; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
AbstractThe goal of the campaign design service city is to facilitate the public in public service. Further research conducted with qualitative research methods that will conduct interviews, observation, documentation, and literacy in order to obtain the data used to support the drafting of an ad campaign. Analysis of data using multiple lifetimes, namely data reduction, panyajuan data, and conclusions. After the data is analyzed, it was found a design concept or design keyword advertising campaign is